2021
DOI: 10.31949/jcp.v7i1.2394
|View full text |Cite
|
Sign up to set email alerts
|

Analisis Gimik Ketidakadilan Melalui Pendidikan Berbasis Literasi Kritis Di Sekolah Dasar

Abstract: The problem of this research is that there is still a lack of application of critical literacy-based learning processes in elementary schools, especially those that raise criticism of power and injustice. The purpose of this study is to analyze the phenomenon of injustice that often occurs in the community through critical literacy education in elementary schools. The research method used is a case study which is expected to be able to reveal and describe in depth how students can interrogate texts and find se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
1
0
3

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 17 publications
(19 reference statements)
0
1
0
3
Order By: Relevance
“…(Sari & Purwanta, 2021). It is suggested that a hybrid learning model can maximize students' understanding, their connection with their teachers, make learning enjoyable, and put them at the center of the learning process Febnesia et al, 2021;Harun et al, 2021;Rachmawati et al, 2022). This perspective is consistent with the constructivist theory of learning, which considers students as active participants in the process of gaining knowledge.…”
Section: Introductionmentioning
confidence: 87%
“…(Sari & Purwanta, 2021). It is suggested that a hybrid learning model can maximize students' understanding, their connection with their teachers, make learning enjoyable, and put them at the center of the learning process Febnesia et al, 2021;Harun et al, 2021;Rachmawati et al, 2022). This perspective is consistent with the constructivist theory of learning, which considers students as active participants in the process of gaining knowledge.…”
Section: Introductionmentioning
confidence: 87%
“…Kelompok online learning adalah kelompok yang melakukan pembelajaran dari rumah sedangkan kelompok face-to-face adalah kelompok yang langsung melaksanakan pembelajaran di kelas. Rachmawati et al, (2022) Model pembelajaran Hybrid dapat menumbuhkan kemampuan literasi digital peserta didik dalam domain afektif, kognitif dan psikomotorik. Penelitian ini berimplikasi terhadap penelitian yang bertujuan untuk dapat mempublikasikan kemampuan literasi digital peserta didik sekolah dasar.…”
Section: Pendahuluanunclassified
“…Penelitian ini berimplikasi terhadap penelitian yang bertujuan untuk dapat mempublikasikan kemampuan literasi digital peserta didik sekolah dasar. (Rachmawati et al, 2022). Nurhasanah (2021) Penelitian lain yang menerapkan model Hybrid learning mengatakan bahwa hal ini dapat membuat pembelajaran menjadi efektif.…”
Section: Pendahuluanunclassified
See 1 more Smart Citation